2023
DOI: 10.3390/ijerph20032570
|View full text |Cite
|
Sign up to set email alerts
|

Relation between VT1, VT2, and VO2max with the Special Wrestling Fitness Test in Youth Wrestlers: A Short Report

Abstract: This study investigated the relationship between peak oxygen uptake and ventilatory threshold 1 (VT1) and 2 (VT2) with the Special Wrestling Fitness Test variables. Thirteen wrestlers (male: six; female: seven) of Olympic freestyle wrestling were assessed. The Pearson’s correlation coefficient (p < 0.05) was used to establish the relationship between variables. A positive correlation was found between VT1 with throws in set B (r = 0.77; p = 0.002; 95%CI = 0.37–0.93), total throws (r = 0.73; p = 0.004; 95%CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Specifically, SWFT is intermittent and consists of three rounds of 30 s maximum dummy throws with 20 s rest between the rounds [10]. Indeed, it has been reported that SWFT evoked cardiac and metabolic responses similar to ones after a wrestling match (i.e., maximal heart rate and blood lactate concentration of 10-20 mmol/L) and are associated with submaximal aerobic performance variables [11,12]. However, it predominantly evaluates the anaerobic glycolytic system, in which most of the actions are performed during the wrestling match [13].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, SWFT is intermittent and consists of three rounds of 30 s maximum dummy throws with 20 s rest between the rounds [10]. Indeed, it has been reported that SWFT evoked cardiac and metabolic responses similar to ones after a wrestling match (i.e., maximal heart rate and blood lactate concentration of 10-20 mmol/L) and are associated with submaximal aerobic performance variables [11,12]. However, it predominantly evaluates the anaerobic glycolytic system, in which most of the actions are performed during the wrestling match [13].…”
Section: Introductionmentioning
confidence: 99%